2020
DOI: 10.4081/ejtm.2020.9311
|View full text |Cite
|
Sign up to set email alerts
|

Muscle hypertrophy and muscle strength: dependent or independent variables? A provocative review

Abstract: The question whether the muscle hypertrophy induced by resistance training, hormone administration or genetic manipulation is accompanied by a proportional increase in muscle strength is still open. This review summarizes and analyses data obtained in human and rodent muscles in studies that have monitored in parallel changes in muscle size and changes in muscle force, measured in isometric contractions in vivo, in isolated muscles ex vivo (in rodents) and in single muscle fibers. Although a general positive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 76 publications
(101 reference statements)
1
28
0
2
Order By: Relevance
“…The need of sports-specic measure is highlighted for example by the possible counterintuitive eects of hypertrophy to strength levels described in recent research. Reggiani et al [664] showed that the increase in muscle mass did not necessarily lead to increase in strength and vice versa [664], and in worst case, the increase in muscle mass was shown to decrease strength production [664,718]. There also seems to exist multiple types of muscle hypertrophy [664,820], with the concept of task-specic hypertrophy [820] becoming relevant when trying to transfer the gains from strength training program to improvements in the particular sport of the athlete [906].…”
Section: Precision Strength Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…The need of sports-specic measure is highlighted for example by the possible counterintuitive eects of hypertrophy to strength levels described in recent research. Reggiani et al [664] showed that the increase in muscle mass did not necessarily lead to increase in strength and vice versa [664], and in worst case, the increase in muscle mass was shown to decrease strength production [664,718]. There also seems to exist multiple types of muscle hypertrophy [664,820], with the concept of task-specic hypertrophy [820] becoming relevant when trying to transfer the gains from strength training program to improvements in the particular sport of the athlete [906].…”
Section: Precision Strength Trainingmentioning
confidence: 99%
“…Reggiani et al [664] showed that the increase in muscle mass did not necessarily lead to increase in strength and vice versa [664], and in worst case, the increase in muscle mass was shown to decrease strength production [664,718]. There also seems to exist multiple types of muscle hypertrophy [664,820], with the concept of task-specic hypertrophy [820] becoming relevant when trying to transfer the gains from strength training program to improvements in the particular sport of the athlete [906]. For instance sports as dierent as combat sports [485,765] and ballet [16,180,818], can be beneted for similar plyometric/ballistic training for explosive force production [906] mixed with some maximum strength training.…”
Section: Precision Strength Trainingmentioning
confidence: 99%
“…Resistance training increases variables associated with muscle hypertrophy and strength (reviewed in [1]). However, the morphological adaptations that occur in myofibers during resistance training have not been fully elucidated [2,3]. It is generally assumed that increases in muscle fiber cross-sectional area (fCSA) with weeks to months of training coincides with the proportional expansion of all intracellular components (i.e., conventional hypertrophy).…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic mechanisms might also be related to the observation that some individuals seem to have less malleable muscles than others, i.e. exercise resistance (17)(18)(19)).…”
Section: Introductionmentioning
confidence: 99%